Potential Requirement of Positron Emission Tomography Apparatuses in Asia and Latin America Including Mexico - Watanabe, Naoyuki; Padhy, Ajit Kumar; Oku, Shinya; Sasaki, Yasuhito (World Journal of Nuclear Medicine, 2013)
The number of positron emission tomography (PET) machines has been increasing in regions of East-, Southeast-, and South-Asia as well as in Latin America including Mexico. This study was performed to assess the potential requirement of PET machines in 19 countries which already use PET in the aforementioned regions. Data on the number of PET machines and internationally available characteristics of the restrictive countries such as the land area, the total population, the gross national income (GNI), and the average life span of inhabitants were obtained from IAEA, UN, WB, and WHO. Correlation between the number of PET machines and the characteristics of each country was evaluated. The potentially required number of PET machines, which was obtained by adjusting the number of PET machines with statistically significant, correlative characteristics of each country, standardized on the state of Japan, were compared. The number of PET machines could be significantly correlated to the GNI of a country and the average life span of its inhabitants (P < 0.05). Based on Japan, most of the countries in the regions would require considerably more PET machines. With installation of the potentially required number of PET machines in each of the countries, the number of PET machine per 106 population would increase by 1.1- to 12-fold, in comparison with the current situation. With regards to the potentially required number of PET machines, most of the countries in these regions may require a considerable increase of PET machines. Nevertheless, some countries in the Asia seem to require outside assistance such as international support in order to introduce PET and enhance the efficacy of their health services.
Keywords: Asia; Latin America; positron emission tomography; positron emission tomography/computed tomography